ADKAR Change Management: A Cross-Sectional Qualitative Focus Group to Describe Perceptions of Factors that Motivate Volunteers in a South African Environmental Organisation - Dorrofield, Kendall (The IIE, 2017)
Understanding the motivation behind volunteers is a key requirement for effective management and retention of volunteers within an NGO. A South African environmental organisation has limited understanding on the types of volunteers or volunteer motivational factors and limited knowledge on the effectiveness of management tools to improve volunteer relationships. This reduces their volunteer workforce, posing a problem. In response, a study was undertaken to describe the motivational factors of volunteers, identify types of volunteers and obtain recommendations for the improvement of volunteer motivation. To facilitate this, the Multi-Paradigm model of volunteering and the ADKAR model of change were utilised. The qualitative and descriptive nature of the study required a focus group approach to obtain an in-depth analysis of motivational factors from managers and volunteers who were selected through convenience and purposive sampling. It was determined that the current level of volunteer motivation seems to be lacking, with a strong concern for volunteers feeling unenthusiastic. Managerial and research implications indicate that volunteer motivation could be improved with a new volunteer management strategy. The ADKAR model of change was utilised and incorporated with findings into a framework that could take the environmental organisation through the change management process.
Keywords: Volunteers; ADKAR Model; Volunteer management; Non-government organisation